NONVERBAL COMMUNICATION AND ITS INFLUENCE ON FIRST IMPRESSION FORMATION - Salam; Yanti Setianti; Eka Sartika; Rahma Helal Al_ Jbour (Adisam Publisher, 2024)
Nonverbal communication is a way for humans to communicate without using language aspects. To communicate nonverbally, a person can use two channels, namely the visible channel and the paralingual channel. Nonverbal behavior in an interaction always communicates something. Even though when we meet new people we will communicate verbally, we need to realize that non-verbal communication also occurs and continues along with verbal communication. Even small things like eye movements, facial expressions, clothing, and body movements still influence other people's perceptions of us. First impressions and nonverbal communication are closely related in building other people's perceptions of us and also our perceptions of other people. The research was carried out using the literature study method. A literature review was used to collect data and information related to nonverbal communication and its influence on first impression formation. This research discusses the definition of nonverbal communication, theories of first impression formation, and the relationship between nonverbal communication and first impression formation.